How Do Teachers Differentiate Instruction Through Materials in a Colombian Rural Zone? - Castiblanco, Valentina (2023)
This research study aims to investigate how teachers implement strategies of  differentiated instruction through materials in their classrooms by taking into consideration the diverse students’ profiles. In this phenomenological qualitative article a total of six (6) EFL educators from Pensilvania (Caldas) participated in this investigation, and data was collected through class observations and semi-structured interviews. The results explore the teachers' level of understanding about differentiation, the training they had received on materials' development and the variety of resources provided for each institution, the aspects they contemplate when creating/designing and adapting materials, and the way in which differentiation through materials was carried out in the classroom. In the conclusion of the article, the importance of providing teachers with the necessary resources is emphasized, as well as the necessity for professional development opportunities, and ongoing support to help them meet the student’s needs.